Android Application Dictionary of English Terms for Mathematics Learning - Muniri Muniri; Galandaru Swalaganata (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
Mathematical terms in English often confuse students with their meanings. In its application, the impact on students' difficulties in understanding the concepts being studied. Students also have a problem in making useful conclusions while the books in English-language textbooks. These things make most Mathematics education students low-motivation and challenging to understand the concepts and basic mathematics derived from English-language texts. The term dictionary can be an alternative solution that can be used to overcome the problems. In general, the term dictionary discusses terms that are not common in a field. This Android application also provides a specific explanation of the terms that are the main search words. Android applications that have been developed are named RIGA. RIGA has 100 words or phrases in English and explanations and 100 words or terms in Indonesian along with answers. This study uses qualitative and quantitative data types. Qualitative data were obtained using a questionnaire in the form of suggestions and criticisms given by the test subjects. Meanwhile, quantitative data were obtained from questionnaire distribution scores from the test subjects. The results show that the results of validation by media experts and field trials produce valid results. Thus, it can claim that RIGA can use for the teaching and learning process.